Induction chemotherapy integrated treatment programs for locally advanced cancers - Aigner, K. (Karl) 1947-; Stephens, Fred (Springer Berlin, 2011)
Induction chemotherapy, as part of an integrated plan of management for locally advanced cancers, is being practised throughout the world in independent, isolated departments in universities, teaching hospitals, and clinical schools. Frequently, however, teams are relatively unaware of the work being undertaken in other institutions, and this situation may slow further progress. This book aims to present the full range of management techniques and practices used in induction chemotherapy within one accessible volume. It provides up-to-date information on the pioneering and cutting edge practices employed in different institutions and documents the advantages of integrated treatment schedules. Patient selection is discussed, and each of the cancer types for which induction therapy has proved important is considered in detail. All who are responsible for the treatment of patients with locally advanced cancers will find this book to be an invaluable source of information. It will be particularly interesting for specialist oncologists aiming to set up and develop fully comprehensive cancer centres and for health administrators wishing to learn about the benefits of establishing such centres in strategic locations.